Review Article: Histological Description of Hepars that Experience Fatty Liver - Mulianti, Rizki; Linawati, Ni Made (Indonesian Journal of Global Health Research, 2024)
The liver is one of the most vital organs and the largest gland, weighing approximately 1500 grams or 2.5% of the total adult body weight. One of the liver's functions is to metabolize nutrients such as fat, protein, and carbohydrates. Fats are synthesized from carbohydrates and proteins, mainly in the liver. Fat function as a source of energy provides essential fatty acids, and plays an important role in dissolving vitamins. A high-fat diet (HFD) is a diet that involves consuming fatty and high-cholesterol foods which can have the risk of causing an increase in lipid levels in the blood, known as hyperlipidemia. Excessive accumulation of fat in liver cells is called fatty liver. Histologically, Non-alcoholic Fatty Liver Disease (NAFLD) is categorized into two types, namely Non-alcoholic Fatty Liver (NAFL) which shows fatty liver without evidence of inflammation in the form of swelling of hepatocyte cells, and Non-alcoholic Steatohepatitis (NASH), namely the presence of fatty liver accompanied by inflammation in the form of swelling of hepatocyte cells, with or without fibrosis.